Navigation path extraction for inter-row robots in Panax notoginseng shade house based on Im-YOLOv5s - Tan, Yu; Su, Wei; Zhao, Lijun; Lai, Qinghui; Wang, Chenglin; Jiang, Jin; Wang, Yongjie; Li, Peihang (Frontiers in Plant Science, 2023)
The accurate extraction of navigation paths is crucial for the automated navigation of agricultural robots. Navigation line extraction in complex environments such as Panax notoginseng shade house can be challenging due to factors including similar colors between the fork rows and soil, and the shadows cast by shade nets. In this paper, we propose a new method for navigation line extraction based on deep learning and least squares (DL-LS) algorithms. We improve the YOLOv5s algorithm by introducing MobileNetv3 and ECANet, achieving an average detection accuracy (mean average precision) of 94.9% with the Im-YOLOv5s model. Compared to YOLOv5s, Im-YOLOv5s improves the average accuracy and frame rate by 1.9% and 27.7%, respectively, and the weight size is reduced by 47.9%. The trained model detects the seven-fork roots in the effective area between rows and uses the root point substitution method to determine the coordinates of the localization base points of the seven-fork root points. The seven-fork column lines on both sides of the plant monopoly are fitted using the least squares method. Experimental results reveal the ability of DL-LS to accurately extract seven-fork row lines, with a maximum deviation of the navigation baseline row direction of 1.64°, meeting the requirements of robot navigation line extraction. Our proposed method provides a basis for the intelligent mechanization of Panax notoginseng planting.